2013
DOI: 10.3892/ijmm.2013.1538
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-mesenchymal transition is necessary for acquired resistance to cisplatin and increases the metastatic potential of nasopharyngeal carcinoma cells

Abstract: Radiotherapy and adjuvant cisplatin (DDP) chemotherapy are standard approaches used in the treatment of nasopharyngeal carcinoma (NPC). However, resistance to chemotherapy has recently become more common, resulting in the failure of this combination therapy for NPC. The aim of the present study was to assess the cellular morphology, motility and molecular changes in DDP-resistant NPC cells in relation to epithelial-mesenchymal transition (EMT). CNE2 cells were continuously exposed to increasing doses of DDP to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 27 publications
4
33
0
Order By: Relevance
“…It has been demonstrated that Slug serves a role in the radioresistance of several types of cancer (31,32). However, the mechanisms underlying the radioresistance of cancer remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that Slug serves a role in the radioresistance of several types of cancer (31,32). However, the mechanisms underlying the radioresistance of cancer remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Tumour cells able to survive chemotherapy treatment exhibit an EMT phenotype. In NPC, paclitaxel- and cisplatin-resistant NPC cells transform into a mesenchymal phenotype (23,24). In the present study, NPC cells underwent characteristic morphological and molecular transformations, such as EMT, upon cisplatin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…EMT has also been correlated with the drug resistance characteristics of cancer cells. Tamoxifen-resistant MCF-7 cells showed aggressive and invasive behavior that could be reversed upon the inhibition of the autocrine EGFR pathway, also known to be involved in EMT (3,(13)(14)(15). Despite the wealth of existing data on the role of EMT in cancer metastasis, its clear picture, diagnostic, and therapeutic targets are yet to be clearly elucidated.…”
Section: Introductionmentioning
confidence: 99%